Synthesis of Isotopic Labelled Paracetamol Benzoate‐d3 and Its Application in the Determination of Paracetamol. Issue 13 (3rd April 2023) - Demirel, Rabia; Erarpat, Sezin; Bodur, Süleyman; Günkara, Ömer Tahir; Bakırdere, Sezgin; Turak, Fatma
Abstract: This study proposed a precise/accurate analytical method for the paracetamol (PCT) determination in human serum/urine matrices. PCT was simultaneously derivatized and preconcentrated by dispersive liquid‐liquid microextraction (DLLME). Benzoyl chloride dissolved in dichloromethane was used as derivatization agent in the extraction solvent. Quadruple isotope dilution (QID) method with three calibration mixtures (A*B‐x, x=1, 2, 3) and one sample mixture (AB) was performed to enhance the method accuracy and precision. In our research laboratory, paracetamol benzoate‐ d3 (PCT benzoate‐ d3 ) was synthesized and used as isotopically labelled substance (B) to conduct QID method. After the combination of QID and DLLME‐GC‐MS systems, percent recovery results for human serum/urine matrices were found to be 99.3–101.0 % and 98.8–99.9 %, respectively. Abstract : Quadruple isotope dilution method, which provides excellent quantitative results, was applied using the synthesized isotopically labelled material (paracetamol benzoate‐ d3 ) to determine paracetamol in serum and urine samples.